Code-Mixing Analysis in the Song Lyrics of “Korban Janji” by Guyon Waton: A Sociolinguistic Study - Khusnul Irma; Citra Dewi Sangdia Pitaloka; Nabila Nur Ardella; Devito Andharu (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
Music is an art form that adds color to life through melody and sound. The song “Korban Janji” by Guyon Waton belongs to the dangdut genre, which has gained popularity among young people because its lyrics often relate to the listeners’ personal experiences. The researcher found a unique feature in this song—namely, the use of two languages in its lyrics: Indonesian and Javanese. This study is a descriptive qualitative research, which interprets and explains the data in detail. The lyrics of “Korban Janji” by Guyon Waton serve as the main object of the study. The sampling technique used is purposive sampling, while the triangulation method applied includes both data triangulation and theory triangulation. The data analysis technique employed is descriptive analysis, and the data were collected using two techniques: reading and note-taking. The purpose of this study is to identify the types of code-mixing found in the lyrics of “Korban Janji”, determine which languages are used, and interpret the messages conveyed through the song. The results of this study show that there is code-mixing in the lyrics, consisting of inner code-mixing (Javanese and Indonesia)